Dispatch Problems Due to Ramp Rate Constraints: Bottleneck Analysis and Solutions - Han, X. S.; Gooi, H. B.; Venkatesh, B. (2003)
This paper proposes a dispatch technique based on the analysis of the system ramp-up/down megawatts (MW). If a dispatch is feasible, it can be shown that the total unavailable ramp-up MW of all the slow units in any future time intervals must be less than or equal to the MW difference between the maximum system MW capacity and the load demand at the end of study intervals. Likewise, the same can be said for the total unavailable ramp-down MW of all the slow units. These two constraints can be used to guide the system away from infeasible dispatch.